Getting to yes [compact disc, unabridged] : negotiating agreement without giving in - Fisher, Roger, 1922-2012; Ury, William; Patton, Bruce (Simon & Schuster Audio, 2011)
A straightforward, universally applicable method for negotiating personal and professional disputes without getting taken -- and without getting angry.